HUBUNGAN PENGETAHUAN, SIKAP DAN DUKUNGAN SUAMI TERHADAP KEPATUHAN PEMERIKSAAN ANTENATAL CARE (ANC) PADA IBU HAMIL DI KECAMATAN LOA KULU KABUPATEN KUTAI KARTA NEGARA - Irfansyah Baharuddin Pakki (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2018)
AbstractBackground : The 2007 IDHS data recorded an MMR in Indonesia reaching 228 per 100,000 live births. The 2015 RPJMN target is 118 per 100,000 live births. Antenatal Care Coverage (ANC) is an examination conducted by pregnant woman to health worker, pregnant woman contact to main health officer with midwife.According to a report by East Kalimantan Provincial Health Office 2016, ANC coverage is 86.34%. Data from Health Office of Regency of Kutai Kartanegara 74,8%. This figure is still below the target of 95%. From the data of Public Health centreat Loa Kulu in 2015, the target number 623 and the number of visits of 491 people pregnant, it is indicated that the ANC coverage has not reached the target.Objectives : the researcher wanted to know the factors related to the health of pregnant women in Loa Kulu distric by measuring the knowledge of pregnant mother about Antenatal Care, attitudes and husband support to the obedience of pregnant mother in doing Antenatal Care.This type of research is obeservasional research and is an analytical survey with Cross Sectional Research Method : This research was conducted on May-July 2016 in Loa Kulu distric of Kutai Kartanegara Regency. The sample taken is the number of pregnant women in Trimester III (pregnancy 28-39 weeks) which amounted to 105 people.The result of the research : shows that there is a correlation of knowledge on maternal ANC compliance with P value 0,002. There is relationship of attitude of pregnant mother to Compliance ANC with value of P value: 0,026. There is a relationship of husband support to maternal ANC Compliance with P value: 0,027 <0,05Conclusion : There is a relationship between knowledge, attitudes and husband support with the obedience of pregnant mother in doing Antenatal Care (ANC). It is better for the officers to give counseling or socialization about Antenatal Care (ANC), pregnancy risk not only in Public Health centre, Posyandu, and other Health Facilities, but more deeply in the groups of recitation and arisan. Keywords : pregnant mother, obedience, Antenatal Care (ANC)